Uji penetrasi jaringan wireless dan IoT dengan tools open - source pada lingkungan virtual - Hafiz Fadhillah; Faris An Nura; Langlang Soeltanul Aulia Aurelsosa; Teuku Farhan Damiri; Muhammad Subhan; Muhammad Zada Zayyan (JIKUM: Jurnal Ilmu Komputer, 2026)
Wireless network security and Internet of Things (IoT) device vulnerabilities have become critical issues in the digital era, especially with the growing reliance on smart devices in household, industrial, and urban environments. Many IoT devices and Wi-Fi networks currently in use remain susceptible to various attacks such as sniffing, spoofing, and brute-force, which can be exploited by malicious actors to steal sensitive information or gain unauthorized control of devices remotely. This study aims to conduct penetration testing on wireless systems and IoT devices within a safe and controlled virtual environment to identify potential security loopholes. The methodology involves setting up a virtual testbed using VirtualBox and the Kali Linux operating system, employing open-source tools such as Aircrack-ng, Nmap, Bettercap, and Wireshark. Attack simulations were carried out on wireless network configurations and virtual IoT devices under common scenarios such as credential theft, traffic surveillance, and denial-of-service (DoS) attempts. The test results indicate that several IoT devices remain highly vulnerable to basic attacks such as sniffing and brute-force login attempts, while wireless networks using WPA2 encryption are also exploitable under certain conditions. These findings highlight the urgent need to improve network security through stronger encryption standards, network segmentation, and device hardening. This study is expected to serve as a reference for developing open-source-based cybersecurity defense systems to protect IoT ecosystems from increasingly sophisticated threats.